2018
DOI: 10.5406/amerjpsyc.131.1.0065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Narcissism and Extreme Altruism

Abstract: Extreme altruism is defined as prosocial behavior that violates social norms or the law. Little research has been done on this phenomenon, although research into related areas suggests that, surprisingly, extreme altruistic activities may be associated with traits traditionally associated with narcissism. This relationship was explored by comparing members of the public, people involved in prosocial activities within socially and legally accepted realms, and members of the Real-Life Superhero (RLSH) movement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…The current study provides a broad perspective on the interindividual differences in rulebreaking by investigating how personality links with behaviours and cognitive processes in rule-breakers and rule-followers. Analogous to previous literature, we found that grandiose is more pronounced in rule-breakers than rule-followers [105]. Grandiose narcissism is characterized by self-importance, feelings of superiority, as well as exhibitionism [100,106].…”
Section: Personality Traits Underlying Interindividual Differences In...supporting
confidence: 87%
See 1 more Smart Citation
“…The current study provides a broad perspective on the interindividual differences in rulebreaking by investigating how personality links with behaviours and cognitive processes in rule-breakers and rule-followers. Analogous to previous literature, we found that grandiose is more pronounced in rule-breakers than rule-followers [105]. Grandiose narcissism is characterized by self-importance, feelings of superiority, as well as exhibitionism [100,106].…”
Section: Personality Traits Underlying Interindividual Differences In...supporting
confidence: 87%
“…Indeed, narcissistic leaders are susceptible to violate norms as they are more likely to be innovative, but also to engage in unethical rule-breaking [79]. Moreover, grandiose narcissism has also been related to pro-social rule-breaking because individuals who are narcissists have the psychological need for grandiose fantasy, sacrificing, self-enhancement, and devaluing rules [105]. Narcissistic individuals believe that there are no limits to achieve their goals and that they are in control of their destiny, which makes them more prompt to violate norms to benefit themselves [107][108][109].…”
Section: Personality Traits Underlying Interindividual Differences In...mentioning
confidence: 99%
“…When comparing children born in the 2000s to their grandparents, Brown (2017) noted that " [m]illennials (born between early 1980s and 2004) are the most narcissistic". On the other hand, the demands of the modern life may easily lead to someone labeled as narcissistic when trying to advance in life without showing altruism or empathy (White, Szabo, & Tiliopoulos, 2018). To some extent, this kind of behavior is natural in this century.…”
Section: Introductionmentioning
confidence: 99%
“…Potwierdzają to badania fenga, Zhanga i Zhonga (2022), którzy wykazali, że zachowania altruistyczne, jakie w przypadku omawianych badań prezentuje styl Ciepły-Zgodny, nie korelowały z negatywnym perfekcjonizmem. Ponadto w badaniach potwierdzono, że skrajnemu altruizmowi często towarzyszy zaburzenie narcystyczne, w skład którego wchodzi wielkościowość (White, Szabo, Tiliopoulos, 2018). Narcystyczne osobowości wykazują także wiele empatycznych cech, które pomagają tworzyć im ciepły wizerunek (Jezierska-Geburczyk, 2020).…”
Section: Dyskusjaunclassified